A Dead Gene Walking: Convergent Degeneration of a Clade of MADS-Box Genes in Crucifers. (25th July 2018) - Hoffmeier, Andrea; Gramzow, Lydia; Bhide, Amey S; Kottenhagen, Nina; Greifenstein, Andreas; Schubert, Olesia; Mummenhoff, Klaus; Becker, Annette; Theißen, Günter
Abstract: Genes are "born, " and eventually they "die." These processes shape the phenotypic evolution of organisms and are hence of great biological interest. If genes die in plants, they generally do so quite rapidly. Here, we describe the fate of GOA -like genes that evolve in a dramatically different manner. GOA -like genes belong to the subfamily of Bsister genes of MIKC-type MADS-box genes. Typical MIKC-type genes encode conserved transcription factors controlling plant development. We show that ABS -like genes, a clade of Bsister genes, are indeed highly conserved in crucifers (Brassicaceae) maintaining the ancestral function of Bsister genes in ovule and seed development. In contrast, their closest paralogs, the GOA -like genes, have been undergoing convergent gene death in Brassicaceae. Intriguingly, erosion of GOA -like genes occurred after millions of years of coexistence with ABS -like genes. We thus describe Delayed Convergent Asymmetric Degeneration, a so far neglected but possibly frequent pattern of duplicate gene evolution that does not fit classical scenarios. Delayed Convergent Asymmetric Degeneration of GOA -like genes may have been initiated by a reduction in the expression of an ancestral GOA -like gene in the stem group of Brassicaceae and driven by dosage subfunctionalization. Our findings have profound implications for gene annotations in genomics, interpreting patterns of gene evolution and using genes in phylogeny reconstructions of species.